Factors Influencing the Propensity to Contract out Health and Human Services in Response to Government Cutbacks: Evidence from US Counties - Min-Hyu Kim (Transylvanian Review of Administrative Sciences, 2019)
Government agencies worldwide have faced budget cutbacks. Possible effects of budget cutbacks on the propensity to contract out have been discussed repeatedly; however, empirical evaluations are lacking. This study tests the contingency theory regarding the main factors that influence the propensity to contract out health and human services in response to fiscal stress: cutback levels, training and development, political factors, diversity as a goal, and the role of unions. The empirical analyses used a nationwide survey of health and human services directors in United States (U.S.) county governments, merged from different sources. The findings suggested that managers’ perceptions of cutback levels are a vital predictor of the propensity to contract out health and human services, and multiple factors have varied influences on their decision to do so in cutback situations. Implications for effective contracting strategies to maintain health and human service delivery, as well as preserving a balanced budget, are discussed.